The relationship between information technology (IT) capability and performance of Islamic banking branches in Kedah from the perspectives of Maqasid Al-Shariah - Afif Zuhri, Muhammad Khodri Harahap (2015)
The purpose of this study is to investigate the relationship between IT capability and the performance of Islamic Banking Branches in Kedah. The study is focuses on Islamic banking branches in Kedah. IT capability in the relationship of banks performance. The IT capability dimension include IT knowledge, IT operations and IT objects. The questionnaires were sent directly to branches and collected by hand. Disproportionate stratified random sampling was used for sample selection. 63 questionnaires were sent to manager of Islamic Banking, 59 samples were returned but only 57 samples were used for data analysis. The data was analyzed using ‘Statistical Package for Social Science’ SPSS version 21. Collectively, the result shows that the IT capability are able to influence overall performance of Islamic banking branches in Kedah and other three (3) dimension of performance (educating individual, establishing justice and public interest). All of the dimension of the IT capability can influence the performance of the Islamic banking. Therefore, the manager of the Islamic banking in Kedah branches should focus on this kind of implementation which is IT capability in order to enhance the performance of their banks. the outcome of this study provide the important insights to both managers and researchers for further understanding about IT capability and performance of Islamic Banking